The youth eco-projekt in the framework of the International triennial of the graphics design “The 4th Block" (Pedagogy of Higher and Secondary Education, 2006)
The youth eco-projekt (nomination of the sixth triennial of the ecological poster "The 4th Block") deals with the actual tasks of the contemporary art and determined its role.
Keywords: youth cco-projekt; The 4th Block; videoart; O. Veklenko